2015
DOI: 10.4085/1062-6050-51.1.08
|View full text |Cite
|
Sign up to set email alerts
|

Methods and Descriptive Epidemiology of Services Provided by Athletic Trainers in High Schools: The National Athletic Treatment, Injury and Outcomes Network Study

Abstract: Context:Research is limited on the extent and nature of the care provided by athletic trainers (ATs) to student-athletes in the high school setting.Objective: To describe the methods of the National Athletic Treatment, Injury and Outcomes Network (NATION) project and provide the descriptive epidemiology of AT services for injury care in 27 high school sports.Design: Descriptive epidemiology study. Setting: Athletic training room (ATR) visits and AT services data collected in 147 high schools from 26 states.Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 11 publications
0
49
0
Order By: Relevance
“…21 Furthermore, the authors of a recent study from the National Athletic Treatment, Injury and Outcomes Network (NATION) reported that although time-loss injuries accounted for a larger number of visits and services per injury than nontime-loss injuries, the latter required more services per visit. 22 Our findings regarding services for current injuries provide additional insight, as one-third of all daily encounters were related to current injuries and required taping, ice-or hot-pack application, or treatment services. Together, these results indicate that ATs may spend a considerable amount of time managing nontimeloss injuries due to the greater volume and amount of care associated with nontime-loss injuries compared with timeloss injuries.…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, the authors of a recent study from the National Athletic Treatment, Injury and Outcomes Network (NATION) reported that although time-loss injuries accounted for a larger number of visits and services per injury than nontime-loss injuries, the latter required more services per visit. 22 Our findings regarding services for current injuries provide additional insight, as one-third of all daily encounters were related to current injuries and required taping, ice-or hot-pack application, or treatment services. Together, these results indicate that ATs may spend a considerable amount of time managing nontimeloss injuries due to the greater volume and amount of care associated with nontime-loss injuries compared with timeloss injuries.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, how do we justify our value, improve our services, and advance our profession in the public health care arena without being able to confidently proclaim what we do? Recent research published in JAT [1][2][3] and derived from research networks focusing on practice-based athletic training is helping us to understand what we do by studying those who do it. In this issue, Lam et al 1 provide a summary from the Athletic Training Practice-Based Research Network (AT-PBRN) that describes the practice characteristics of ATs in the secondary school setting based on more than 36 000 patient encounters in nearly 5000 patients from 34 schools in 10 states.…”
mentioning
confidence: 99%
“…Similarly, in 2015, the initial summaries from the National Athletic Treatment, Injury and Outcomes Network (NATION) were also published in JAT. 2,3 The NATION draws epidemiologic data from 147 high schools across 26 states, with the initial reports representing more than 50 000 injuries and 200 000 athletic training room visits. Establishing these large, practice-based research networks is not a trivial task.…”
mentioning
confidence: 99%
See 2 more Smart Citations